MCU : the reign of Marvel Studios - Robinson, Joanna (Podcaster); Gonzales, Dave (Podcaster); Edwards, Gavin, 1968- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2023)
"The unauthorized, behind-the-scenes story of the stunning rise--and suddenly uncertain reign--of the most transformative cultural phenomenon of our time: the Marvel Cinematic Universe. Marvel Entertainment was a moribund toymaker not even twenty years ago. Today, Marvel Studios is the dominant player both in Hollywood and in global pop culture. How did an upstart studio conquer the world? In MCU, beloved culture writers Joanna Robinson, Dave Gonzales, and Gavin Edwards draw on more than a hundred interviews with actors, producers, directors, and writers to present the definitive chronicle of Marvel Studios and its sole, ongoing production, the Marvel Cinematic Universe. For all its outward success, the studio was forged by near-constant conflict, from the contentious hiring of Robert Downey Jr. for its 2008 debut, Iron Man, all the way up to the disappointment of Ant-Man and the Wasp: Quantumania and shocking departures of multiple Marvel executives in 2023. Throughout, the authors demonstrate that the original genius of Marvel was its resurrection and modification of Hollywood's old studio system. But will it survive its own spectacular achievements? Dishy and authoritative, MCU is the first book to tell the Marvel Studios story in full--and an essential, effervescent account of American mass culture"--